Cytogenetics of the skinks (Reptilia, Scincidae) from Thailand; IV: newly investigated karyotypic features of Lygosoma quadrupes and Scincella melanosticta - Isara Patawang (2018)
© 2017 Dipartimento di Biologia, Università di Firenze. This study analyzed the karyotype of Lygosoma quadrupes and Scincella melanosticta from northeastern Thailand. Mitotic chromosomes were prepared directly from intestinal epithelial cells of three L. quadrupes and nine S. melanosticta. The chromosomes were stained by conventional staining technique. The karyotype was determined for each species based on at least 20 well-spread cells. Both L. quadrupes and S. melanosticta showed the same diploid number of 2n = 30, but differed in identical chromosome morphology. No sex chromosome heteromorphisms were evident in L. quadrupes; in contrast, S. melanosticta showed the ZZ/ZW sex determination system. The respective karyotype formulae of L. quadrupes and S. melanosticta were deduced as: (Formula presented.).